Development of an Undiagnosed Mass Registry: Lessons Learned From Our First 100 Patients - Steven W. Ressler; Ivana T. Croghan; Marlene E. Girardo; John P. Fasolino; Elizabeth A. Gilman; Nate P. Erwin; Nancy L. Dawson; Joan M. Irizarry-Alvarado; Ryan T. Hurt; Karthik Ghosh (Journal of Primary Care & Community Health)
Introduction: The Undiagnosed Mass Clinic (UMC) at our institution is a clinical and research program created to address gaps in the early diagnostic phase of the cancer care continuum for patients with potential malignant neoplasms. All patients referred to the UMC are invited to participate in the UMC registry, which tracks operational and clinical metrics while maintaining a repository of blood and tissue specimens for future research. Methods: We conducted a retrospective cohort study of the first 100 patients enrolled in the UMC registry. We analyzed patient demographics, final diagnoses, and the time from initial consultation to final diagnosis. Results: Most participants were White (86%), non-Hispanic (93%), and married (72%). The mean (SD) age was 64 (13.9) years. The final diagnoses of the masses were categorized as malignant/neoplastic with malignant potential (n = 53), benign (n = 36), or requiring diagnostic surveillance (n = 10). The mean (SD) time from initial consultation to final diagnosis of malignant/neoplastic with malignant potential masses significantly improved from 37.4 (36.6) days for the first 50 participants to 17.3 (19.7) days for the next 50 participants ( P  = .006). Conclusions: These initial insights from the UMC registry will help direct future efforts to improve the care of patients with potential malignant neoplasms.